THE EFFECT OF SERVICE QUALITY AND PROMOTION ON PURCHASE DECISIONS AT DW DIGITAL PRINTING IN MAJALENGKA - Ade Ulfah; Gian Fitralisma; Winda Dwi Yanthi (PT. Berkah Digital Teknologi, 2025)
Purpose: This research aims to determine the influence of service quality and promotion on purchasing decisions at DW Digital Printing, Majalengka Regency. Research Methodology: The study employs quantitative descriptive methods for data collection. Data was gathered through questionnaires distributed to respondents via Google Forms, and hypotheses were calculated using SPSS. The population consisted of DW Digital Printing consumers who had purchased banners, with a sample size of 61 respondents. Results: The findings indicate that for the service quality variable, the t-test results show tcount > ttable (4.513 > 1.671) with a significance level of 0.00 < 0.05. This leads to the rejection of H0 and acceptance of Ha, indicating a positive and significant influence of service quality on purchasing decisions. Conversely, the promotion variable yielded tcount < ttable (1.544 < 1.671) with a significance level of 0.128 > 0.05, resulting in the rejection of H0 and acceptance of Ha, indicating a positive but insignificant influence of promotions on purchasing decisions. The F-test revealed Fcount of 78.488 > Ftable of 2.40 with a significance level of 0.00 < 0.05, leading to the rejection of H0 and acceptance of Ha, suggesting a positive and significant influence of service quality and promotion simultaneously on purchasing decisions. Limitations: This research contributes to the understanding of how service quality and promotional strategies impact consumer purchasing behavior in the digital printing industry, providing insights for businesses to enhance their marketing approaches. Contribution: This research makes a significant contribution to understanding the impact of service quality and promotion on purchasing decisions in the digital printing industry. The findings can be utilized by printing business owners, particularly DW Digital Printing, to formulate more effective marketing strategies. By enhancing service quality and optimizing promotional strategies, companies are expected to attract more consumers and increase customer loyalty. Furthermore, this study provides insights for academics and future researchers to further explore the relationship between these variables in different contexts, as well as to enrich the existing literature on consumer behavior in the service sector.